CIVIL LEGAL ISSUES OF CRYPTOCURRENCY TRANSACTIONS IN THE PROVISION OF DIGITAL SERVICES - Hazratkulov Odilbek Tursunovich (Scholar Express Journals, 2023)
In turn, it is important to review the laws and legal documents of developed countries that have advanced in the field of digital financial services aimed at regulating this sector.The existence of transactions with cryptocurrencies in the field of digital financial services today, and the fact that this practice is increasingly covering financial relations, today requires conducting research on this issue. In particular, the world is interested in the question of how to regulate the rights and obligations arising from trading or money exchange between users of cryptocurrencies via the Internet. This situation requires legal support for the movement of cryptocurrencies in financial transactions and their use by individuals. Cryptocurrencies raise many questions about these legal issues.
Keywords: integration; technological revolution; financial technology